ADAPTING THE VILLAIN: A CASE STUDY OF GEORGE WICKHAM - Maggio, Sandra Sirangelo; Vogel, Luana Hastenteufel (Revista de Letras Norte@mentos, 2023)
This article focuses on the portrayal of the antagonist George Wickham, from the novel Pride and Prejudice, to its adaptation to the webseries The Lizzie Bennet Diaries. The analysis delineates the main characteristics that make him an antagonistic character and investigates how they are adapted to the webseries. First, we present a brief summary of the context of production of the adaptation; after, we look to what makes Wickham such a charming antagonist in the novel and how these character traits were treated in the adaptation; finally, we compare both works in order to identify how the antagonist was adapted.